Connected Strategy building continuous customer relationships for competitive advantage - Siggelkow, Nicolaj; Terwiesch, Christian (Harvard Business Review Press, 2019)
Prologue. The magic of connected strategy -- The connected strategy framework -- Part I. The rewards of connected strategies: Breaking the trade-off between superior customer experience and lowering costs -- Workshop 1: Using connectivity to provide superior customer experiences at lower costs -- Part II. Creating connected customer relationships: Recognize, request and respond: building connected customer experiences -- Repeat: building customer relationships to create competitive advantage -- Workshop 2: Building connected customer relationships -- Part III. Creating connected delivery models: Designing connection architectures -- Revenue models for connected strategies -- Technology infrastructure for connected strategies -- Workshop 3: Building your connected delivery model
Keywords: Beziehungsmarketing; Marketing; Kundenmanagement; Kundenbindung; Sales & Marketing; Business strategy; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Marketing / General; Relationship marketing; Customer services - Technological innovations; Communication in consumer education